2019
DOI: 10.1016/j.chembiol.2019.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and Characterization of a Nitroreductase Capable of Conferring Bacterial Resistance to Chloramphenicol

Abstract: Highlights d Bacteria can resist chloramphenicol via reduction, but the causal genes are unknown d nfsB nitroreductase expression can confer chloramphenicol resistance in E. coli d H. influenzae NfsB quickly reduces chloramphenicol to amino-chloramphenicol in vitro d Metronidazole potentiates chloramphenicol activity against nitro reducing E. coli

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
73
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(85 citation statements)
references
References 58 publications
1
73
1
2
Order By: Relevance
“…This might confer a selective advantage via a higher potential to recycle NAD(P) as electron acceptors for the (fermentative) energy and intermediary metabolism, or via the possibility to inactivate toxic xenobiotics produced by gut commensal microorganisms. Recently, similar findings were published concerning the Haemophilus influenzae nitroreductase NfsB reducing and thereby inactivating chloramphenicol (Crofts et al, ). On the other hand, the reduction in nitro compounds to toxic intermediates renders organisms expressing such nitroreductases susceptible to nitro drugs and therefore constitutes a selective disadvantage.…”
Section: Discussionsupporting
confidence: 68%
“…This might confer a selective advantage via a higher potential to recycle NAD(P) as electron acceptors for the (fermentative) energy and intermediary metabolism, or via the possibility to inactivate toxic xenobiotics produced by gut commensal microorganisms. Recently, similar findings were published concerning the Haemophilus influenzae nitroreductase NfsB reducing and thereby inactivating chloramphenicol (Crofts et al, ). On the other hand, the reduction in nitro compounds to toxic intermediates renders organisms expressing such nitroreductases susceptible to nitro drugs and therefore constitutes a selective disadvantage.…”
Section: Discussionsupporting
confidence: 68%
“…Resistance to chloramphenicol was reported in five STEC strains, being different from that reported for industrialized species in Chile, where AMR was detected for a wider variety of drugs at phenotypical analysis ( 47 ). Resistance to the phenicols is mainly due to the presence of cat genes, encoding for chloramphenicol acetyltransferases, specific to chloramphenicol, or to the presence of cml genes, encoding for efflux pumps, among other mechanism, such as nfs B nitroreductase expression ( 81 ).…”
Section: Discussionmentioning
confidence: 99%
“…NfsB_Ec has received near-exclusive attention as a prodrug-converting NTR for both cancer gene therapy and targeted cell ablation applications 1 . However, recent evidence suggests "NTR 1.0" is a relatively inefficient NTR compared to orthologous enzymes 23,33,34 . In particular, we showed that active site residues F70 and F108 impede activity with the 5-nitroimidazole PET probe SN33623 and that rational substitution of these residues yielded generic improvements in 5-nitroimidazole reduction 23 .…”
Section: Discussionmentioning
confidence: 99%